A distributed joint topology control and forwarding protocol in MANETs using game theory. (2016) - Govarchinghaleh, Yaghoub Alizadeh; Sabaei, Masoud; Tavallaie, Omid
In mobile ad-hoc networks (MANETs), each node tries to maximise its utility in the network and saves its limited resources including energy and bandwidth due to different ownerships and selfish behaviour, which can cause nodes not to cooperate in network tasks such as topology control and packet forwarding and it affects performance of all tasks of the network. Thus, the induced topology lacks favourable specifications including connectivity, optimised energy consumption. Topology control and packet forwarding mutually affect each other. In addition, retrieving complete information about MANETs is challenging because of mobility and high signalling cost. In this paper, the issue of nodes selfishness in topology control and packet forwarding has been addressed by game theory. It is assumed that nodes have local information. Simulation results show that the proposed model decreases the signalling cost of the topology control, increases the network life and dramatically decreases the transmission power variance.